Use of Complementary and Alternative Medicine among Cancer Patients - Neupane, Suchita; Gautam, Roshani; Sharma, Sujan; Shrestha, Lava (Journal of Institute of Medicine Nepal, 2024)
Introduction Complementary and alternative medicine (CAM) use is common among cancer patients with the hope to manage symptoms arising from the cancer related treatment or to improve the quality of life. In this study, we aimed to describe various CAM practices among cancer patients. Methods A descriptive cross-sectional study was conducted in Bhaktapur Cancer Hospital. Convenient sampling technique was used to select the participants. Data was collected from cancer patients attending in out-patient department of Bhaktapur Cancer Hospital with a structured questionnaire. The collected data and analyzed using Statistical Package for the Social Sciences (SPSS) version 16. Results The use of CAM was found in 40.7% (37/91) of the studied cancer patients. Among them, Ayurveda 18 (56.2%) was the most common type of CAM used. Among CAM users, the most common reason for using CAM was to reduce side effects of cancer related treatment (22, 59.4%). The majority of the respondents 33 (89.1%) were satisfied with CAM use. Only 14 (37.8%) of respondents consulted with their doctor about the initiation of CAM use. Gynecological cancer 38 (41.7%) was the most common site of cancer seen among the respondents followed by respiratory 18 (19.7%) and gastro-intestinal 17 (18.6%) respectively. Twenty eight (30.8%) of the respondents were in the third stage of cancer. Conclusion Less than half of the cancer patients were using CAM, Ayurvedic medicine being the most common form. Majority of the users were satisfied with CAM use. Further studies on potential risk and benefits associated with CAM therapy is needed as its use has been increasing.